Mobilization, Repression and Exile of Young Nicaraguan Activists - Gómez-Abarca, Carlos de Jesús (2019)
This article analyzes the socio-political crisis that began in Nicaragua in April 2018 through the meanings and political practices of young activists framed in three interrelated processes: the role of young people in mobilization, repression and exile of young activists. The work is based on a series of interviews made in Nicaragua and Costa Rica between 2018 and 2019, and secondary sources that include journalistic research papers and reports from human rights organizations. In conclusion, the importance of social mobilizations is recognized as an expression of social change and as a mark for the new generations of activists.